2011
DOI: 10.1080/17470218.2010.524304
|View full text |Cite
|
Sign up to set email alerts
|

No commonality between attentional capture and attentional blink

Abstract: Visual search for a unique target is impaired when a salient distractor is presented (attentional capture). This phenomenon is said to occur because attention is diverted to a distractor before it reaches the target. Similarly, perception of the second of two targets embedded in a rapid stream of nontargets is impaired, suggesting attentional deprivation due to the processing of the first target (attentional blink). We examined whether these phenomena emerge from a common underlying attentional mechanism by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The results of these correlation analyses align with existing research suggesting that the mechanisms by which attention is captured or held by salient stimuli differ depending on whether the stimulus is a target or distractor23 and whether it appears before or after a target stimulus16. The present work nonetheless provides evidence for a retroactive EAB in a dual-target task that, like the forward EAB, is differentially induced by erotic and gory stimuli.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of these correlation analyses align with existing research suggesting that the mechanisms by which attention is captured or held by salient stimuli differ depending on whether the stimulus is a target or distractor23 and whether it appears before or after a target stimulus16. The present work nonetheless provides evidence for a retroactive EAB in a dual-target task that, like the forward EAB, is differentially induced by erotic and gory stimuli.…”
Section: Discussionsupporting
confidence: 86%
“…participants high in trait harm avoidance9) would be most susceptible to the other form. This conclusion is limited by the fact that it is based on a null result, but seems reasonable given the limited data available at present and the conclusions of other studies using a similar approach1623.…”
Section: Discussionmentioning
confidence: 73%
“…In seeking to better understand how goal-driven and stimulus-driven factors supply our visual experience, researchers have begun to scrutinize the considerable variability in individuals' abilities to resist attentional distraction (Kane et al, 2001; Fukuda and Vogel, 2009, 2011; Kanai et al, 2011; Kawahara and Kihara, 2011). Primarily, these studies have focused on variability in the goal-driven component of attentional control.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, van Zoest and Donk (2005) presented all stimuli simultaneously in a wide area of the search display (i.e., spatial search task), whereas we presented individual stimuli sequentially at the same spatial location (i.e., temporal search task). Kawahara and Kihara (2011) concluded that two different mechanisms may underlie the two different types of attentional capture (i.e., spatial search and temporal search tasks) by showing no correlation between spatial and temporal capture under the singleton detection mode. Therefore, if the same issue applies to the present results, different temporal scales may be required for attentional set to be available under the singleton detection mode across two different search tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the use of a wide range of procedures. For example, Kawahara and Kihara (2011) found that different mechanisms may separately underlie the temporal and spatial capture phenomena. Thus, to simplify the discussion, the present study focused on temporal attentional capture.…”
mentioning
confidence: 99%